Description of Sarsilatona cf. fernandoi (Rane, 1983) (Crustacea: Cladocera: Sididae) found in the south of Vietnam - Korovchinsky, Nikolai M. (Zootaxa, 2011)
The representatives of the rare genus Sarsilatona close to originally poorly described S. fernandoi (Rane, 1983) from Central India (Madhya Pradesh State) are studied on the basis of female specimens from two localities in the south of Vietnam. Their exact species assignment remains to be vague due to inability to investigate the type material. The studied specimens differ from all other species of the genus in presence of only small denticles, not setules, on the sensory seta of antennules. S. cf. fernandoi resembles S. serricauda (Sars, 1901) in presence of large dorsal postabdominal outgrowths but differs from the latter in shorter antennules, lack of a large prominence on the posterior side of antennal basipodite, presence of setules, not small denticles, on the ventral valve margins, more numerous anal teeth in each cluster, and less numerous and thicker clusters of spinules near postero-ventral valve margins. The representatives of S. fernandoi s.l. seem to be widely distributed in tropical Asia, from India to Vietnam, preferring small water bodies. Superficially similar representatives of the genus from Africa probably belong to a yet undescribed new species.